Diseño automatizado de cimentaciones superficiales con MATLAB - Nápoles Leal, Javier Guzmán (Universidad Central “Marta Abreu” de Las Villas. Facultad de Construcciones. Departamento de Ingeniería Civil, 2016)
Software is presented programmed in MATLAB for the design automated geotechnical and structural of isolated rectangular superficial foundations, keeping in mind the application of the method of the States Limits to evaluate the security of the same ones, determining the cost of the solution. In the work design examples are also included that they contribute to understand the form of using the system and they are compared with the design results obtained by other calculation leaves presented by other authors, like form of validating them. This system constitutes an element inside a wider system directed to the optimization of structural groups that uses the potentialities of MATLAB for it, of there its relevancy. In the conception of the software the last advances of the method of the States Limits are used applied to the geotechnical and structural design of the foundations. The global result will be a tool that attends the engineer or student to solve problems in the field of the optimum design of the foundations or structures in general.
Keywords: Diseño de Cimentaciones Superficiales; Software MATLAB; Diseño Geotéctino y Estructural; Design; Foundations (Soil Engineering)